PENDIDIKAN KESEHATAN MAKANAN BERGIZI BAGI IBU HAMIL DAN BAYI BALITA SEBAGAI UPAYA PENCEGAHAN STUNTING DI DESA PUKDALE - Pili Mangngi, Atalia; Babys, Isna Yuswela; Manek, Brigita Dina; Gusman, Avelina Paskalia; Satiti, Diah Ayu Dwi; Alang, Ermi Lilianda; Atapukang, Fitri; Fernandez, Ninick Corea; Erni, Bernadeta (Jurnal Abdi Insani, 2025)
ABSTRAC Malnutrition is one of the factors that increases the risk of stunting in children. Providing adequate nutrition from conception and providing complementary foods appropriate to the child's nutritional needs are key ways to prevent stunting. This initiative aims to provide health education on nutritious food for pregnant women and mothers of toddlers as a preventative measure. This activity was carried out at the Pukdale village office with the target being pregnant women, mothers with babies, mothers of toddlers and couples of childbearing age and the general public in Pukdale village. Counseling or education to the community by involving stakeholders as supporters of the realization of a healthy generation. This activity was attended by a target of 50 people consisting of pregnant women, mothers with babies and toddlers and also by the general public. All participants were involved enthusiastically and interacted with the speakers through discussion and Q&A sessions. This activity had a very positive impact on all participants because there was an increase in knowledge on the results of the questionnaire examination.